Declaration of Conformity of Excitation System of Synchronous Machines - Ćirić, Zoran; Ristić, Mihajlo (Proceedings, Electrical engineering institute "Nikola Tesla", 2023)
The paper presents a comprehensive complex model for the Declaration of Conformity of the Excitation System. The necessary projects for conformity assessment, standardization, accreditation and metrology are given. Some testing and compliance modules are listed. A part of the test according to the CB scheme of Low-voltage switchgear and controlgear assemblies for the excitation system Tesla ES 7000A is presented, which is according to valid standards, and for nominal currents up to 7000 A. A part of the test according to the CB scheme of electromagnetic compatibility for the Tesla ES excitation regulator is presented. The Declaration of Conformity of the Tesla ES 1600 excitation system is presented